UNRAVELING THE ROLE OF COMPENSATION AND WORK ENVIRONMENT IN EMPLOYEE PERFORMANCE: THE MEDIATING EFFECT OF EMPLOYEE ENGAGEMENT AT PT WAHYU MANDIRI AMARA CIPTA - Amran Wahyudiah; Didik Hadiyatno; Nurlia (Faculty of Economics and Business, Universitas Warmadewa, 2026)
This study aims to examine the relationships between compensation, work environment, employee engagement, and employee performance, as well as to investigate the mediating role of employee engagement. A quantitative approach was employed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Data were collected from 48 employees of PT Wahyu Mandiri Amara Cipta through a structured questionnaire. The findings reveal that compensation and work environment do not have a significant direct effect on employee performance. However, both variables significantly influence employee engagement, with the work environment demonstrating the strongest effect. Contrary to expectations, employee engagement does not significantly affect employee performance. Furthermore, the mediating role of employee engagement in linking compensation and work environment to employee performance is not supported. These results suggest that while organizational factors such as compensation and work environment are effective in enhancing employee engagement, they are insufficient to improve performance outcomes directly or indirectly. The findings highlight a gap between psychological engagement and actual performance, particularly in operational and target-driven organizational contexts. This study contributes to the literature by providing empirical evidence that challenges the commonly assumed mediating role of employee engagement in influencing performance. Practically, organizations are encouraged to complement engagement strategies with performance management systems and skill development initiatives to achieve optimal performance outcomes.